The future of sex and gender in psychology: Five challenges to the gender binary - Hyde, Janet Shibley; Bigler, Rebecca S.; Joel, Daphna; Tate, Charlotte Chucky; van Anders, Sari M. (American Psychologist, 2019)
The view that humans comprise only two types of beings, women and men, a framework that is sometimes referred to as the “gender binary,” played a profound role in shaping the history of psychological science. In recent years, serious challenges to the gender binary have arisen from both academic research and social activism. This review describes 5 sets of empirical findings, spanning multiple disciplines, that fundamentally undermine the gender binary. These sources of evidence include neuroscience findings that refute sexual dimorphism of the human brain; behavioral neuroendocrinology findings that challenge the notion of genetically fixed, nonoverlapping, sexually dimorphic hormonal systems; psychological findings that highlight the similarities between men and women; psychological research on transgender and nonbinary individuals’ identities and experiences; and developmental research suggesting that the tendency to view gender/sex as a meaningful, binary category is culturally determined and malleable. Costs associated with reliance on the gender binary and recommendations for future research, as well as clinical practice, are outlined. (PsycINFO Database Record (c) 2019 APA, all rights reserved).
Keywords: LGBTQIA2+; activisme; analyse critique; approches et analyses; cours; discipline; discours dominant; hétérosexisme; identité sexuelle; identités LGBTQIA2+; neurosciences; premier cycle; psy4910; psychologie; queer; revue de la littérature; sciences humaines; sexe/genre; systèmes d'oppressions; thématiques; épistémologie; études de genres

The Routledge handbook of epistemic injustice - Kidd, Ian James; Medina, José; Pohlhaus, Gaile M. (Routledge handbooks in philosophy, 2017)
In the era of information and communication, issues of misinformation and miscommunication are more pressing than ever. Epistemic injustice--one of the most important and ground-breaking subjects to have emerged in philosophy in recent years--refers to those forms of unfair treatment that relate to issues of knowledge, understanding, and participation in communicative practices. The Routledge Handbook of Epistemic Injustice is an outstanding reference source to the key topics, problems, and debates in this exciting subject. The first collection of its kind, it comprises over thirty chapters by a team of international contributors, divided into five parts: Core Concepts; Liberatory Epistemologies and Axes of Oppression; Schools of Thought and Subfields within Epistemology; Socio-political, Ethical, and Psychological Dimensions of Knowing; Case Studies of Epistemic Injustice. As well as fundamental topics such as testimonial and hermeneutic injustice and epistemic trust the Handbook includes chapters on important issues such as social and virtue epistemology, objectivity and objectification, implicit bias, and gender and race. Also included are chapters on areas in applied ethics and philosophy, such as law, education, and healthcare. The Routledge Handbook of Epistemic Injustice is essential reading for students and researchers in ethics, epistemology, political philosophy, feminist theory, and philosophy of race. It will also be very useful for those in related fields, such as cultural studies, sociology, education, and law.
Keywords: approches et analyses; capacitisme; cours; cycles supérieurs; discipline; fem9000; hétérosexisme; injustices épistémiques; intersectionnalité; outils; ouvrages de références; philosophie; racisme; santé; sciences humaines; sexisme; systèmes d'oppressions; thématiques; violences; épistémologie; éthique; études critiques de la race; études critiques du handicap

Les représentations de figures genderqueers en art actuel : identités et sexualités : lieux de subjectivités dissidentes - Dubois, Anne-Marie (Université du Québec à Montréal, 2014)
La volonté de ce projet de maîtrise consiste à analyser la manière dont les représentations de figures genderqueers en art actuel participent à une réflexion critique des notions d'identité et de sexualité comme lieux privilégiés de résistance à l'hétéronormativité. Je souhaite démontrer à quel point la représentation du corps queerisé peut agir comme espace stratégique d'une repolitisation de la sexualité et de l'identité et ainsi contribuer à une micropolitique de résistance. Par le truchement des politiques et théories queers et féministes, les pratiques artistiques polymorphes de J.J. Levine, Dorothée Smith, Nina Arsenault et Virginie Jourdain questionnent et critiquent l'hétéronormativité et ses discours pour en dévoiler les principaux axiomes idéologiques et ainsi en déconstruire l'apparente naturalité. Dans l'objectif de comprendre et d'articuler les enjeux que sous-tendent les théories féministes et queers actuelles, je vais m'attarder plus spécifiquement à en circonscrire les prémisses enracinées dans le contexte postmoderne. En revisitant des auteurs clés tels Michel Foucault et Judith Butler, je souhaite mettre en lumière leurs contributions intellectuelles et théoriques pour la constitution d'une pensée critique des identités et des sexualités. Les représentations de figures genderqueers en art actuel participent ainsi d'une déconstruction des présupposés immanents de l'hétéronormativité dont le genre est en quelque sorte l'ancrage ontologique. En jouant de ces codes hégémoniques de manière à en désamorcer la violence symbolique, Smith, Levine, Jourdain et Arsenault participent à une remise en cause des concepts même d'identité et de sexualité pour nous faire entrevoir de possibles subjectivations dissidentes. À la source de mes réflexions, il y a ainsi une volonté épistémologique de produire un savoir mutant, progéniture androgyne d'une multitude de penseurs qui n'ont de cesse de nourrir la discipline de l'histoire de l'art. Ce mémoire est donc le mariage polygame de méthodologies hétéroclites dont l'objectif ultime est la production d'un savoir queer riche et sensible. ______________________________________________________________________________ MOTS-CLÉS DE L’AUTEUR : postmodernisme, queer, identités, sexualités, genderqueer, J.J. Levine, Dorothée Smith, Virginie Jourdain, Nina Arsenault, micropolitique de résistance, subjectivités dissidentes, hétérotopies identitaires, hétéronormativité, pharmacopornographie.
Keywords: 1900-1999; IREF; amériques; approches et analyses; canada; discipline; europe; france; féminisme postmoderne; histoire de l'art; hétérosexisme; identités LGBTQIA2+; mémoires/thèses; périodes historiques; queer; ressource en ligne; régions géographiques; sciences humaines; sexualité; systèmes d'oppressions; thématiques; épistémologie